In-service Training Programmes Related to Inclusive Education: Perspectives of Elementary School Teachers - Ponnusamy, P.; Sankar, Smitha (Voices of Teachers and Teacher Educators, 2022)
Expertise of teachers is considered to be a very important factor in implementing their academic inputs in the educational system and motivating students to become useful members of the society. In-service training programmes, especially, in inclusive education, support the teachers handling children with special needs and to overcome the challenges in their field. The purpose of this study is to investigate the reflections of elementary school teachers on designing and implementation of the in-service training programmes related to inclusive education. The required data were collected from the 305 elementary school teachers randomly selected from the state of Kerala in India. The main finding of the study reveals that majority of elementary school teachers viewed that the in-service training programmes related to inclusive education were at a satisfactory level.